PENGARUH LEVERAGE, STRUKTUR KEPEMILIKAN, DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Widya Atri Faranita; Darsono Darsono (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of leverage, ownership structure, and audit quality on earnings management. This study use propotion of managerial ownership, institutional ownership, and foreign ownership as a component of ownership structure, as well as auditor independence and audit firm size as a component of audit quality. This study uses secondary data taken form Indonesia Stock Exchange in period 2012-2015. The selected companies to be research samples are basic industry and chemical sector, miscellaneous industry sector, and consumer goods industry sector. The sample population in this study is 561 companies. Based on the criteria specified, the number of samples in this study is 112 companies. The method of analysis used in this study is multiple regression analysis.The results showed that the leverage, auditor independence, and audit firm size have a positive effect on earnings management. Managerial ownership, institutional ownership, and foreign ownership have no effect on earnings management.